In situ surface protection of lithium metal anode in Lithium–Selenium disulfide batteries with ionic liquid-based electrolytes. (March 2020) - Dong, Panpan; Zhang, Xiahui; Cha, Younghwan; Lee, Jung-In; Song, Min-Kyu
Abstract: Selenium disulfide (SeS2 )–based composites have received much attention as a promising cathode material for high-energy lithium metal batteries due to their higher theoretical capacity (1342 mAh g −1 ) than that of selenium (675 mAh g −1 ) and less severe shuttle effect than that of sulfur. However, Li–SeS2 batteries still suffer from two main challenges: (1) the development of stabilized lithium metal anodes maintaining the functional interface during cycling and (2) the high-performance SeS2 cathodes allowing long cycle life with good rate capability. Herein, we report a dense, stable LiF-rich, and conductive Li3 N-rich protection layer formed in situ on lithium metal surface by the co-presence of pyrrolidinium-based ionic liquid and LiNO3 in the electrolyte. Such unique protective layer led to little morphological changes of lithium anode over cycling and effectively mitigated the growth of lithium dendrites and the unwanted side reactions with soluble cathode intermediates. The protected lithium metal anode also showed good cycling stability of repeated plating/stripping over 400 h at a practical current density of 2 mA cm −2, which is important for the safe operation of lithium metal batteries. When paired with 3D interconnected hierarchical SeS2 cathodes, Li–SeS2 battery showed good cycling performance over 500 cycles with much improved Coulombic efficiency (>98.9%) with the capacity decay of less than 0.08% per cycle after stabilization. These findings suggest a promise of stabilized lithium metal anode through the in situ formation of protective layer coupled with functional cathode design, taking one step closer toward the development of high-energy Li metal batteries with long cycle life. Graphical abstract: Image 1 Highlights: A stable and conductive SEI layer was formed in situ on Li metal by the co-presence of Py14 TFSI and LiNO3 in electrolyte. The protected Li metal anode showed good cycling stability of plating/stripping over 400 h at current density of 2 mA cm −2 . 3D interconnected, hierarchical SeS2 @KB600 nanocomposite was synthesized via a facile two-step heat treatment. Li–SeS2 battery showed much suppressed shuttle effects with Py14 TFSI-LiNO3 electrolyte at current density of 67.1 mA g –1 . Li–SeS2 battery showed good cycling performance up to 500 cycles with overall coulombic efficiency of >98.9% at 1 A g –1 .